Improving environmental sustainability in Hospitality and Tourism: the key strategies - Oliveira, Mónica (2024)
The Hotel and Tourism Industry has experienced profound changes in recent years and has been one of the sectors most affected by COVID-19. With the return of tourist activity, many companies went back to their normal routines, but the sector has changed dramatically. Tourists have new expectations, needs, and priorities, and sustainability is the one that is most emphasised, particularly when it comes to excessive water consumption, misuse of energy, and poorly utilised waste. The industry has a unique opportunity to recognise the importance of sustainability and define strategies to guarantee customer satisfaction, in symbiosis with environmental concerns and the preservation of the planet for future generations. This study aims to characterise the good strategies and practices for environmental sustainability in Hospitality and Tourism, namely in terms of energy, water, and waste. The purpose is to present the procedures and processes that lead to greater sustainability performance and to accomplish this a focus group was organised, with 2 hospitality stakeholders, 2 environmental groups stakeholders, and 2 VET (Vocational Education and Training) stakeholders, to discuss and identify the main factors directly related to the excessive use of water and energy and the poor treatment of waste and ranked by the participants. The meeting was done face-to-face, lasted 3 hours, and was based on their expertise and good practices. The Hospitality and Tourism Industry is conscious of its ecological footprint, namely in terms of energy efficiency, water conservation, and waste management. Considering energy, some examples were given such as electricity-saving practices, using LED bulbs, occupancy sensors, and automatic light controls. With respect to water, it is mandatory to install low-slip faucets and shower heads, reduce laundry and cleaning, and recycle water that can be reused for irrigation or toilet flushing, reducing the use of fresh water. The research presented contributions to the growing Knowledge on this topic, and the findings propose a straightforward guide for managers in the Hospitality and Tourism industry. Further research is endorsed to reinforce the value of environmental sustainability and to involve a greater range of stakeholders with different profiles in the sector.